2017
DOI: 10.1007/s11042-017-4348-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and predicting the popularity of online news based on temporal and content-related features

Abstract: As the market of globally available online news is large and still growing, there is a strong competition between online publishers in order to reach the largest possible audience. Therefore an intelligent online publishing strategy is of the highest importance to publishers. A prerequisite for being able to optimize any online strategy, is to have trustworthy predictions of how popular new online content may become. This paper presents a novel methodology to model and predict the popularity of online news. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Expression on social media posts has been studied for various platforms, such as Facebook (Van Canneyt et al 2018;Srinivasan et al 2013;, Instagram (Jaakonmäki, Müller, and vom Brocke 2017;Ferrara, Interdonato, andTagarelli 2014), Twitter (Van Canneyt et al 2018;Bandari, Asur, and Huberman 2012;, YouTube (Ma, Yan, and Chen 2017;Vallet et al 2015), and Reddit (Stoddard 2015). However, the previous work has mostly focused on views, likes, shares, and comments on the same platform, with little focus on how these engagement metrics compare across platforms and how public the user engagement is.…”
Section: Related Work User Engagement Modelingmentioning
confidence: 99%
“…Expression on social media posts has been studied for various platforms, such as Facebook (Van Canneyt et al 2018;Srinivasan et al 2013;, Instagram (Jaakonmäki, Müller, and vom Brocke 2017;Ferrara, Interdonato, andTagarelli 2014), Twitter (Van Canneyt et al 2018;Bandari, Asur, and Huberman 2012;, YouTube (Ma, Yan, and Chen 2017;Vallet et al 2015), and Reddit (Stoddard 2015). However, the previous work has mostly focused on views, likes, shares, and comments on the same platform, with little focus on how these engagement metrics compare across platforms and how public the user engagement is.…”
Section: Related Work User Engagement Modelingmentioning
confidence: 99%
“…Platform recommendation algorithms also favor videos released in specified timeframes. Canneyt et al found that the time when information was posted on Twitter and Facebook largely determined its initial popularity [17].…”
Section: Related Work 21 Factors Influencing Popularitymentioning
confidence: 99%
“…They extracted features of historical diffusion and multimedia meta information, and proposed a concept drift-based mechanism to conduct popularity prediction. Canneyt et al [40] firstly analyzed view patterns of online news on multiple platforms, and then predicted future popularity by the combination of features related to content, meta-data, and the temporal behavior. Rizoiu et al [41] developed a Hawkes intensity process, which links exogenous inputs from Twitter, and endogenous responses within YouTube, to predict the popularity of online contents.…”
Section: Related Workmentioning
confidence: 99%